Convergence and economic growth in Mexico - Díaz Bautista, Alejandro (Frontera Norte, 2017)
Recently, much attention has been paid in the literature on economic growth to the phenomenon of conditional convergence or the tendency of regional economies with lower level incomes to grow faster, conditional on their rate of factor accumulation. This study uses the standard neoclassical growth theory, to obtain the empirical approximation of the convergence hypothesis to human capital between the 31 states and the Federal District in Mexico, using educational indices. The study finds that the annual rate of convergence of human capital per capita to Mexico ranges from 3.55% to 4.58%. It also estimates the convergence of income per capita conditional on human capital variables. RESUMEN Recientemente, se ha puesto mucha atención en lo escrito sobre crecimiento económico, el fenómeno de convergencia condicional o la tendencia de las economías regionales con niveles bajos de ingreso a un crecimiento rápido, como condicional en su tasa de acumulación de factores. El estudio utiliza teorías neoclásicas de crecimiento estandarizadas, para obtener la aproximación empírica de la hipótesis de convergencia sobre el capital humano entre los 31 estados y el Distrito Federal en México, utilizando índices de educación. El estudio encuentra que la tasa anual de convergencia de capital humano per cápita en México oscila del 3.55 al 4.58 por ciento. También estima la convergencia de ingreso per cápita condicional en variables de capital humano.